CMA of Wideband Circularly Polarized Metasurface Antenna for 5G Wireless Technology - Nathapat Supreeyatitikul; Panisa Keowsawat; Rachen Kanahna; Titipong Lertwiriyaprapa; Chuwong Phongcharoenpanich (My University, 2023)
This paper proposes a compact circularly polarized (CP) metasurface (MTS) antenna for 5G wireless communications. The characteristic mode analysis (CMA) is utilized to characterize the antenna structure. The proposed CP MTS antenna consisted of two substrate layers of FR-4 type. The upper substrate layer contained multi-shaped MTS cells. The lower substrate layer functioned as an aperture-coupled feed. The evolution of the proposed CP MTS antenna comprised of four stages: MTS-1 (conventional MTS scheme), MTS-2, MTS-3, and MTS-4 (proposed antenna). The conventional MTS scheme generated the two MS modes (Modes 1 and 2) with orthogonal surface current and radiations. Besides, the surface current of Modes 3 and 4 is traveled along the edges of the conventional MTS scheme. To eliminate those surface currents, the multi-shaped is utilized which sits around the conventional MTS scheme (MTS-2, 3, and 4). When an aperture-coupled feed is applied, the ARBW of the MTS-1 is improved. The simulated IBW and ARBW at 3.5 GHz (center frequency) are 43.4% (3.4–4.92 GHz) and 37.14% (3.28–4.58), respectively. The maximum gain is 7.25 dBic at 3.6 GHz. The radiation characteristic is right-hand circular polarization, rendering the proposed CP MTS antenna reasonable for 5G technology.
Keywords: Antenna Design and Analysis; Advanced Antenna and Metasurface Technologies; Energy Harvesting in Wireless Networks